A New Technique of Achilles Tendon Rupture Repaired by Double Transverse Mini‐incision to Avoid Sural Nerve Injury: A Consecutive Retrospective Study. Issue 2 (26th December 2022) - Xu, Lihu; Jin, Jiaxin; Liu, Zhongcheng; Wu, Meng; Peng, Bo; Jiang, Jin; Liu, Guangyao; He, Jinwen; White, Sylvia; Xia, Yayi
Abstract : Objective: Percutaneous suture is a classic technique used in Achilles tendon repair. However, the complication rates surrounding the sural nerve remain relatively high. Modified percutaneous repair technology can effectively avoid these complications; however, the surgical procedure is complicated. Hence, the present study was conducted to describe a redesigned repair technique for the Achilles tendon able to avoid sural nerve injury and reduce the complexity of the procedure. Methods: Data of patients with acute primary Achilles tendon rupture at our hospital from January 2019 to May 2020 were included. Subjects with expectations for surgical scarring underwent a minimally invasive‐combined percutaneous puncture technique. The surgical time, requirement for conversion to other technologies, and length of postoperative hospitalization were investigated to assess efficacy. The American Orthopedic Foot & Ankle Society (AOFAS) score and the Arner–Lindholm scale (A‐L scale) were used to assess postoperative clinical outcomes (> 24 months). During the 2‐year follow‐up, MRI was performed to observe the healing of the Achilles tendon. In addition, subjective satisfaction with surgical scar healing was recorded. Results : Twenty consecutive subjects with an average follow‐up of 28.3 ± 4.5 months (range, 24–41) met the inclusion criteria. None of the 20 enrolled patients required a converted surgical approach. The mean surgical time was 26.9 ± 6.47 min (range, 20–44). None of the patients experienced dysesthesia or anesthesia around the sural nerve. No signs of postoperative infections were observed. MRI data showed that the wounds of the Achilles tendon healed completely in all the subjects. The AOFAS score increased from 55.6 ± 11.07 (range, 28–71) preoperatively to 97.8 ± 3.34 (range, 87–100) at the last follow‐up. The A‐L scale showed that 90% of the subjects (n = 18) presented as excellent and 10% of the subjects (n = 2) presented as good, with an excellent/good rate of 100%. Moreover, subjects' satisfaction for surgical scars was 9.1 ± 0.78 (upper limit, 10). Conclusions: The results indicate that this technique can achieve good postoperative function, a small surgical incision, and high scar satisfaction. In addition, this technique should be widely used in suturing Achilles tendon ruptures. Abstract : The present study was conducted to describe a redesigned repair technique of Achilles tendon, which could avoid sural nerve injury and reduce the complexity of the surgery.